Biased Render: Indigenous Algorithmic Embodiment in 3D Worlds. Issue 1 (1st June 2019) - Miner, Joshua D.
Abstract : This article explores the digitality of Indigenous bodies within contemporary 3D video games by mainstream and Indigenous developers. Its analysis relies on a critical examination of digital image synthesis via real-time graphics rendering, which algorithmically generates the visible world onscreen from 3D geometries by mapping textures, generating light and shadow, and simulating perceptual phenomena. At a time when physically based, unbiased rendering methods have made photorealistic styles and open-world structures common across AAA games in general, Indigenous game designers have instead employed simplified "low res" styles. Using bias as an interpretive model, this article unpacks how these designers critique mainstream rendering as a cultural-computational practice whose processes are encoded with cultural biases that frame the relation of player and screen body (avatar). The algorithmic production of digitally modeled bodies, as an essential but masked element of video games, offers a territory where Indigenous developers claim aesthetic presence in the medium.